Speculations on the origin of language - RIZZOLATTI, GIACOMO; CRAIGHERO, LAILA (Gjornâl Furlan des Siencis - Friulian Journal of Science, 2004)
There are two main views on the origin of human language. The first is that it derives from animal’s call, the other from gestures. In the present article we argue that the second view is much more plausible. We discuss first a neurophysiological mechanism, the mirror neuron mechanism, which solves the problem of direct comprehension of action meaning. We discuss then how sounds have been added to gestures and eventually became the main medium of human communication.